A new species of Streptocephalus Baird, 1852 (Crustacea, Branchiopoda) from Peninsular India - Prashant Manohar Katke; Sameer M. Padhye; Avinash Isaac Vanjare (Zoosystematics and Evolution)
The Indian subcontinent contains six of the more than 60 species of the fairy shrimp genus Streptocephalus Baird, 1852. Three of these occur in the western parts of peninsular India. Recent studies from the megadiverse Western Ghats have revealed a seventh Streptocephalus species from the Indian subcontinent and the second from the Northern Western Ghats (NWG). Streptocephalus warliae sp. nov. is described and compared with related South and Southeast Asian species. The males exhibit a distinct triangular basomedial projection at the base of the second antenna distal antennomere, whereas the females have a deep apical notch at the tip of their second antenna. Streptocephalus warliae sp. nov. is so far known only from its type locality and may have a limited geographic range. We provide a modification to the key of Indian Streptocephalus. Considering the increasing urbanisation in the region, we suggest a red listing of the species.